Key Concepts in the Study of Antisemitism
XVIII, 336 p. 5 illus., 4 illus. in color.
Keywords: This volume is designed to assist university faculty and students studying and teaching about antisemitism, racism, and other forms of prejudice. In contrast with similar volumes, it is organized around specific concepts instead of chronology or geography. It promotes conversation about antisemitism across disciplinary, geographic, and thematic lines rather than privileging a single methodological paradigm, a specific academic field, or an overarching narrative. Its twenty-one chapters by leading scholars in diverse fields address the relationship to antisemitism of concepts ranging from Anti-Judaism to Zionism. Each chapter not only traces the history and major scholarly debates around a key concept; it also presents an original argument, points to avenues for further research, and exemplifies a method of investigation.